Redefining Gender: A Literature Review on the Evolution of Gender Roles and Identities Across Cultures in the Great Lakes Region - Mark Paul Diyammi (Eastern African Journal of Humanities and Social Sciences, 2025)
This literature review examines the evolving nature of gender roles and identities across Africa’s Great Lakes region, exploring how modern changes engage with colonial legacies, indigenous knowledge, and global influences. This study employs critical interpretive synthesis (CIS), a qualitative methodology that systematically analyses and reinterprets existing research through a critical lens. Unlike conventional reviews, CIS does not merely summarise evidence but constructs new theoretical understandings. Findings show the region undergoing significant shifts. While colonial binaries persist in some areas, new adaptations are emerging, urban youth redefining masculinity and women claiming spaces in traditionally male domains. Digital platforms act as tools for feminist activism yet also create cultural tensions, while religious institutions both uphold and challenge patriarchal norms. Cultural expression, especially through art, serves as a form of resistance, challenging traditional gender roles. The analysis highlights how local communities develop hybrid approaches to gender justice, blending cultural preservation with progressive change. These strategies challenge both nostalgic traditionalism and the uncritical uptake of Western feminist models, offering alternative pathways for gender transformation. The review concludes with practical recommendations, including decolonising gender education by prioritising indigenous knowledge, developing culturally appropriate digital infrastructure to counter linguistic imperialism, and reforming legal systems through locally relevant epistemologies. Overall, this research emphasises the importance of policies that respect regional specificities while tackling global gender justice issues. It enriches broader debates by showing how gender transformations in the Great Lakes region provide valuable insights into the interplay of culture, power, and identity in postcolonial settings.